Here in the real world ebook - Pennypacker, Sara (2020)
From the author of the highly acclaimed, New York Times bestselling novel Pax comes a gorgeous and moving middle grade novel that is an ode to introverts, dreamers, and misfits everywhere. Ware can't wait to spend summer "off in his own world"—dreaming of knights in the Middle Ages and generally being left alone. But then his parents sign him up for dreaded Rec camp, where he must endure Meaningful Social Interaction and whatever activities so-called "normal" kids do. On his first day Ware meets Jolene, a tough, secretive girl planting a garden in the rubble of an abandoned church next to the camp. Soon he starts skipping Rec, creating a castle-like space of his own in the church lot. Jolene scoffs, calling him a dreamer—he doesn't live in the "real world" like she does. As different as Ware and Jolene are, though, they have one thing in common: for them, the lot is a refuge. But when their sanctuary is threatened, Ware looks to the knights' Code of Chivalry: Thou shalt do battle against unfairness wherever faced with it. Thou shalt be always the champion of the Right and Good—and vows to save the lot. But what does a hero look like in real life? And what can two misfit kids do?